Teaching Essay Writing to the ELT Students’ - Siti Frastiwi; Dina Merris Maya Sari (Jurnal Ilmiah Wahana Pendidikan, 2020)
Essay writing ELT students’ is considered as one of the most important academic courses in asupposed program help develop students’ skill. The research subjects were 11 students of class2019 A STKIP PGRI Sidoarjo English Education study program. The instrument used was aquestionnaire and scoring rubric. The technique for data analysis is qualitative. In analyzingessay writing data with a questionnaire and scoring rubric are as follows. Taking the dataquestionnaire was conducted using 15 questionnaires in a student's response to learning essaywriting with Google Form with answers to yes and no. respondents who answered yes as much84,23% and than respondents who answered no as much 21,22%. Then got data based on scoringrubric was carried out by assessing and correcting the essay writing results of 11 students of class2019 A. The result were assessed using a scoring rubric consisted of 5 aspects, namely format,mechanics, content, organization, grammar and sentence structure. From the description above,the average value was 87.3. This study presents a research report on teaching essay writing to theELT students. The aim is to find out students ability in essay writing and students responses inessay writing classroom.